Sintesis Senyawa Mentil Vanilat dari Vanilin dan Aplikasinya sebagai Parfum - Risnandar, Ade Irfan; Prabawati, Susy Yunita (ALKIMIA, 2019)
Synthesis of menthyl vanilate compound has been carried out and its application asperfume. The synthesis was carried out through oxidation of vanillin using Tollens reagentfollowed by esterification of vanillic acid with menthol. The result of oxidation process wereanalyzed for melting point and characterized using FTIR. Esterification of vanillic acid usingmenthol was carried out by addition of SOCL2 reagent. The synthesized compound wascharacterized using FTIR and Proton Nuclear Magnetic Resonance (1H-NMR) and followedby organoleptic test. Melting point of vanillic acid is 212oC. Identification of vanillic acidwith FTIR is shown that the absorption of C-H aldehyde at wave numbers 2850 and 2750 cm -1 is absence indicating that the aldehyde group of vanillin has been oxidized completely.Esterification of Vanillic acid using menthol with the addition of SOCl2 produces anirreversible reaction and obtained a brown liquid which is mentil vanilat ester compound.Synthesis of menthyl vanilate compound was obtained with yield 48.05%. Identification ofmenthyl vanillate with FTIR showed the absorption of C-O (from Ester) at wave numbers1219 and 1180 cm-1. Identification with 1H NMR showed the peak at chemical shift 0.74-2.16 ppm which is absorption of proton from the substituted menthyl group. Based on theresult of identification using FTIR and 1H NMR spectrophotometers can be concluded thatmenthyl vanillate compound has been successfully synthesized. The result of organoleptic testshowed that 95% of respondents agree that the compound is fragrant, 100% respondents agreethat the the aroma of compound is sharp, and 75% of respondents like the product of thesynthesized compound to be perfume.